IMPLEMENTASI KEAMANAN MIKROTIK MENGUNAKAN METODE SIMPLE PORT KNOCKING PADA SMAN 1 NGANTANG - Firdaus, Nasrul; Fitriawan, Angga (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2018)
A computer network is a group of computers or more that are connected to each other electronically.Network security is currently one of the most important and growing issues.Microtic security at SMAN 1 NGANTANG is still not fully considered, it makes the network administrator nervous about the Brute Force attack.SMAN 1 NGANTANG is a high school located in the poor district of Malang, SMAN 1 NGANTANG has services for students and teachers, namely wifi based on mikrotik.At present the security of mikrotik there has not been prioritized, even the microticists there are still vulnerable to attacks from those who do not have authorization.Because security has not been prioritized, mikrotik there is vulnerable to attacks from outside and inside.Therefore, researchers are interested in implementing the Simple Port Knocking method on the mikrotik server of SMAN 1 NGANTANG.Testing in this study using a router that uses a mikrotik operating system, this study will compare mikrotik without using Simple Port Knocking with mikrotik that use Simple Port Knocking and will be attacked by Brute Force. The results of this study are the comparison table of security mikrotik without using Simple Port Knocking and using Simple Port Knocking. Keywords: Mikrotik Security, Firewall, Simple Port Knocking, Brute Force Method, SMAN 1 NGANTANG